Uji Hambatan Tumorigenesis Sari Buah Merah (Pandanus Conoideus LAM.) Terhadap Tikus Putih Betina Yang Diinduksi 7,12 Dimetilbenz(a)Antrasen (DMBA) - Mun‘im, Abdul; Andrajati, Retnosari; Susilowati, Heni (Majalah Ilmu Kefarmasian, 2006)
Red fruit (Pandanus conoideous Lam.) has been known by public as a medicine for any kind of diseases, among of them is for cancer. To determine the carcinogenesis inhibition effect of red fruit extract , we have examined the effect on 7,12- dimethylbenz[a]anthrasene (DMBA)-induced rat lungs cancer model in female Sprague-Dawley rats. The extract was tested at 0.21 ml/200 g bw; 0.43 ml/200 g bw and 0.88 ml/ 200 g bw. The experiment was terminated at day 120. Lung histology was used to evaluate carcinogenesis inhibition. The result showed that the extract at 0.21 ml/200g bw improved lung carcinogenesis inhibition than other dose.